Equally weighted portfolios vs value weighted portfolios: Reasons for differing betas - Pae, Yuntaek; Sabbaghi, Navid (Journal of Financial Stability, 2015)
We prove that constituent companies’ capital structure and tax shield cause the difference in systematic risk between an equally weighted portfolio and a value weighted portfolio in an efficient market where the CAPM holds. The difference in systematic risk has positive association with component companies’ default risk.